2018
DOI: 10.1186/s13049-018-0543-9
|View full text |Cite
|
Sign up to set email alerts
|

Lightning accidents in the Austrian alps – a 10-year retrospective nationwide analysis

Abstract: BackgroundLightning strikes are rare but potentially lethal. The risk for suffering a lightning strike in a mountain environment is unknown. The aim of this nationwide study was to analyse all lightning accidents in the Austrian Alps from 2005 to 2015, to assess the circumstances of the accident, the injury pattern as well as the outcome.MethodsFrom 2005 to 2015, data from the national Austrian Alpine Police database as well as the Clinical Information System of Innsbruck Medical University Hospital were searc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 24 publications
(37 reference statements)
0
19
0
1
Order By: Relevance
“…For the Austrian Alps, fatalities per year can therefore be summarised as approximately 110 for mountain hiking, 20 for rock climbing, 6 for via ferrata climbing and 5 for mountain biking [18,19]. With 0.7 canyoning-related deaths per year in the Austrian Alps, the absolute mortality is not far away from in the figure for being struck by lightning (0.4 deaths/year) [20]. Of course, incidences are not taken into account for these comparisons.…”
Section: Mortality Approximationmentioning
confidence: 99%
“…For the Austrian Alps, fatalities per year can therefore be summarised as approximately 110 for mountain hiking, 20 for rock climbing, 6 for via ferrata climbing and 5 for mountain biking [18,19]. With 0.7 canyoning-related deaths per year in the Austrian Alps, the absolute mortality is not far away from in the figure for being struck by lightning (0.4 deaths/year) [20]. Of course, incidences are not taken into account for these comparisons.…”
Section: Mortality Approximationmentioning
confidence: 99%
“…These results confirm the likely higher mortality of the transthoracic current transition. [1] Parallel with these findings, Ströhle et al [11] reported 64 patients who were exposed to a lightning strike, indicating that 6.3% of these patients died, and 10.9% had serious injuries. No lung injury was reported in any of the cases in this study.…”
Section: Discussionmentioning
confidence: 87%
“…Avalanches, falls, frostbite, rock falls, or becoming lost are known dangers that go hand in hand with these mountaineering activities [ 5 , 6 , 7 ]. In comparison to these frequent causes of emergencies, less is known about lighting strikes [ 8 ]. While the general risk of being struck by lightning is low, the risk is increased in the mountains due to one’s proximity to the atmosphere [ 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In comparison to these frequent causes of emergencies, less is known about lighting strikes [ 8 ]. While the general risk of being struck by lightning is low, the risk is increased in the mountains due to one’s proximity to the atmosphere [ 8 , 9 , 10 , 11 ]. Lightning strikes are electrical discharges in the earth’s atmosphere [ 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation